Adsorption equilibria of volatile organic compounds on the surface of atmospheric aerosol components - Bogillo, V. I. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
Quantitative “structure – activity” relationships have been proposed between the free adsorption energy, adsorption enthalpy with in the Henry area and at the finite concentrations on the surface of atmospheric aerosol components, and molecular descriptors of volatile organic compounds. Chemical composition of the surface has been demonstrated to exert a substantial effect on the adsorption thermodynamics for the compounds.